WARGA PEDULI AIDS WUJUD PERAN SERTA MASYARAKATDALAM PENANGGULANGAN HIV/AIDS - Argyo Demartoto (Jurnal Analisa Sosiologi, 2018)
The increased HIV/AIDS epidemic makes the social-economic development burden heavier. The objective of research is to analyze public participation in overcoming HIV/AIDS as the manifestation of warga peduli AIDS (local residents concerned about AIDS). The target group in this case study was community and stakeholders such as Kelurahan, Warga Peduli AIDS Administrator, AIDS Commission of Surakarta City, Surakarta Health Service, Solo Plus Peer Support Group, and LSM Peduli AIDS (NGO concerned about AIDS) in Surakarta selected purposively. Data collection was carried out using observation, in-depth interview, and documentation. Data was validated using data source triangulation, and then analyzed using Parsons’ social system theory. The result of research showed that some citizens concerned about AIDS and were active but had not participated much in coping with AIDS, due to their limited knowledge, limited awareness, and fear of undertaking HIV test, less optimal, non-sustainable socialization from AIDS Commission and AIDS-Concerned institution focusing on risk group only, so that people got inadequate information about HIV/AIDS, stigma and discrimination against people with HIV/AIDS. AIDS overcoming needs active role from many parties including government, community, those infected and affected in preventing, treating, mitigating the effect, and developing conducive environment systemically and in integrated manner, in order to achieve the objective.     Keywords: AIDS, Participation, Citizen, Integrated   AbstrakPeningkatan epidemi  HIV/AIDS menyebabkan beban sosial ekonomi pembangunan semakin berat. Tujuan penelitian ini adalah menganalisis peran serta masyarakat dalam penanggulangan HIV/AIDS sebagai wujud warga peduli AIDS. Kelompok sasaran  penelitian studi kasus ini adalah masyarakat dan stakeholders terkait, seperti Kelurahan, pengurus Warga Peduli AIDS,Komisi Penanggulangan AIDS Kota Surakarta, Dinas Kesehatan Surakarta, Kelompok Dukungan Sebaya Solo Plus, LSM Peduli AIDS di Surakarta  yang dipilih secara purposif. Pengumpulan data dengan observasi, wawancara mendalam dan dokumentasi. Triangulasi sumber data untuk menguji validitas data, lalu dianalisis dengan teorisistem sosial Parsons. Hasil penelitian menunjukkan bahwa ada warga yangpeduli AIDS dan aktif, namun banyak yang belum terlibat dalam penanggulangan AIDS, karena minimnya pengetahuan, kesadaran, dan takut melakukan tes HIV, sosialisasi dari Komisi Penanggulangan AIDS dan lembaga peduli AIDSbelum optimal, tidak berkelanjutan dan hanya fokus kelompok berisiko saja, sehingga masyarakat kurang mendapat informasi HIV/AIDS secara menyeluruh,masih ada stigma dan perlakuan diskriminasi terhadap orang dengan HIV/AIDS.Penanggulangan AIDS memerlukan peran aktif multi pihak baik pemerintah, masyarakat, mereka yang terinfeksi dan terdampak dalampencegahan, pengobatan, mitigasi dampak dan pengembangan Iingkungan yang kondusif secara sistemik dan terpadu agar tujuan tercapai. Kata Kunci: AIDS, Partisipasi, Warga, Terpadu